2007
DOI: 10.1002/jcb.21236
|View full text |Cite
|
Sign up to set email alerts
|

CD36 is a novel and potential anti‐fibrogenic target in albumin‐induced renal proximal tubule fibrosis

Abstract: Albumin is not only a risk factor for diabetic nephropathy (DN), but also a therapeutic target. Hence, scientists have long sought ways to elucidate the interactions between albumin and diabetic renal tubule fibrosis. CD36, a surface receptor for thrombospondin-1, has been reported to interact with latent transforming growth factor-beta1 (TGF-beta1) and activate its fibrogenic bioactivity. This study elucidates the interactions between CD36 and renal tubule fibrosis. LLC-PK1 cells were applied to represent ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 28 publications
(34 reference statements)
2
34
0
Order By: Relevance
“…Similar increases in CD36 expression have been observed in LLC-PK 1 porcine PTCs exposed to albumin (43) and in whole kidney homogenates of nephrotic rats (22). Susztak et al (39) reported increased CD36 expression in the kidneys of patients with diabetic nephropathy with a diffuse cellular distribution, very similar to that observed in the nephrotic kidneys in the present study, but no increased expression in the kidneys of patients with FSGS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar increases in CD36 expression have been observed in LLC-PK 1 porcine PTCs exposed to albumin (43) and in whole kidney homogenates of nephrotic rats (22). Susztak et al (39) reported increased CD36 expression in the kidneys of patients with diabetic nephropathy with a diffuse cellular distribution, very similar to that observed in the nephrotic kidneys in the present study, but no increased expression in the kidneys of patients with FSGS.…”
Section: Discussionsupporting
confidence: 89%
“…In human diabetic nephropathy, PTC CD36 expression and apoptosis are positively associated (39). Expression of CD36 in PTC is increased by albumin (43) and following exposure to advanced oxidation protein products (AOPPs). Endocytosis of AOPP-modified human serum albumin by PTC is CD36 dependent (21).…”
mentioning
confidence: 99%
“…50 Blockade of CD36 through RNA silencing in cultured renal proximal tubular cells reduced bioactive TGF-␤1 and fibronectin in the presence of profibrogenic concentrations of albumin. 59 Together, these data suggest that TSP1-mediated activation of latent TGF-␤ is a key factor in diabetic tubulointerstitial fibrosis and proteinuria. The data showing a reduction in renal fibronectin, especially in the interstitium, by LSKL treatment is supportive of a role for TSP1-regulated TGF-␤ activation in tubulointerstitial fibrosis in diabetes.…”
Section: Discussionmentioning
confidence: 82%
“…CD36 has been reported as a receptor of GHS in mediating the cardiovascular action of GH-releasing peptides in the heart (5). It has been reported that CD36 is a novel and potential antifibrogenic target in albumin-induced renal proximal tubule fibrosis (42), and a CD36 synthetic peptide inhibits silica-induced lung fibrosis in mice (34). Our study showed that mRNA expression of CD36 is very low in SHRs and increased to same level of wild-type rats after hexarelin treatment, indicating the involvement of CD36 in the antifibrotic effect of hexarelin.…”
Section: Discussionmentioning
confidence: 99%